(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Andrographis paniculata, a widely used medicinal herb, has been employed for centuries to treat various ailments. This review aims to summarize the literature on A. paniculata, focusing on its therapeutic benefits, chemical properties, pharmacological evaluation, and toxicity. A TLC method has been developed for the determination of Andrographolide in A. paniculata extract.